The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1186/1423-0127-20-35
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation, characterization and toxicity of lipophosphoglycan-polyacrylic acid conjugate for vaccination against leishmaniasis

Abstract: Research on the conjugates of synthetic polyelectrolytes with antigenic molecules, such as proteins, peptides, or carbohydrates, is an attractive area due to their highly immunogenic character in comparison to classical adjuvants. For example, polyacrylic acid (PAA) is a weak polyelectrolyte and has been used in several biomedical applications such as immunological studies, drug delivery, and enzyme immobilization. However, to our knowledge, there are no studies that document immune-stimulant properties of PAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…It is noted that peptides are usually more stable, easier to produce and cheaper than recombinant proteins, although their isolated use as peptide‐based vaccine usually present low protective efficacy due to the immunological restriction to one protein of origin . In the light of our knowledge, the protective characteristics of these vaccine candidates could be improved by increasing the number of doses of the vaccine, the amount of peptide used in each dose and/or even using carrier molecules . In addition, the employ of vaccines combining CD4 + and CD8 + T‐cell epitopes could optimize the protective efficacy of these candidates, when compared to their individual use …”
Section: Discussionmentioning
confidence: 99%
“…It is noted that peptides are usually more stable, easier to produce and cheaper than recombinant proteins, although their isolated use as peptide‐based vaccine usually present low protective efficacy due to the immunological restriction to one protein of origin . In the light of our knowledge, the protective characteristics of these vaccine candidates could be improved by increasing the number of doses of the vaccine, the amount of peptide used in each dose and/or even using carrier molecules . In addition, the employ of vaccines combining CD4 + and CD8 + T‐cell epitopes could optimize the protective efficacy of these candidates, when compared to their individual use …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the proteinase activity of gp63 plays an important role in controlling the process of complement activation, so in a way it provides the parasite with the resistance to cope up with complement-mediated lysis [139]. The parasites are efficient enough for exploiting the macrophage signalling especially the JAK-STAT pathway, the key regulator of the IFN-γ signalling [140].…”
Section: Development Of Vaccinementioning
confidence: 99%
“…A recent study has reported the development of the immunogenic lipophosphoglycan molecule isolated from Leishmania parasites conjugated with PAA. 12 The covalent conjugation of peptide and polymer molecules provides the opportunity for next-generation synthetic vaccines by means of modifying the immunogenicity of the peptide antigens. Accordingly, for the first time, we aimed to synthesize, characterize, and determine the toxicity of the bioconjugate of the peptide of the M2e protein covalently bonded with PAA in order to develop a universal synthetic vaccine prototype against influenza A virus.…”
Section: Introductionmentioning
confidence: 99%